Debt sharing after Covid-19: How the direct involvement of EU institutions could impact the recovery path of a member state - Kieran McQuinn; Petros Varthalitis (The Economic and Social Research Institute (ESRI), 2020)
The likely substantial impact of Covid-19 related measures on the public finances of European countries has prompted an unprecedented call for new and significant policies at a European level to alleviate the pressures on individual member states. The administrative closures adopted across a number of economies has resulted in a complete cessation of certain types of economic activity, a significant increase in unemployment and profound fiscal challenges for the countries in question. In this paper we use a SOE-DSGE model to assess the role European institutions can play in mitigating the negative economic and fiscal effects of the crisis for a particular member state by participating directly in the sovereign debt management of that country. Our results indicate that the direct involvement of EU institutions via sovereign bonds purchases increases the efficiency of the extraordinary fiscal stimulus packages undertaken by member states. A fiscal stimulus at the national level backed by EU financing reduces the output losses in the first year which would otherwise occur. The reduction in the output loss ranges from 0.8 per cent to 1.4 per cent depending on the mix of fiscal policies chosen by the member state. The cumulative reduction in output loss over a five-year horizon could sum to 2.5 per cent to 4.1 per cent depending on the fiscal policy mix chosen.
Keywords: I18; E62; O43; N24; 330; Covid-19; Fiscal Policy; Sovereign Debt; European Union